2022
DOI: 10.1038/s41467-022-29517-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of neuroendocrine transcriptional states in metastatic small cell lung cancers and patient-derived models

Abstract: Molecular subtypes of small cell lung cancer (SCLC) defined by the expression of key transcription regulators have recently been proposed in cell lines and limited number of primary tumors. The clinical and biological implications of neuroendocrine (NE) subtypes in metastatic SCLC, and the extent to which they vary within and between patient tumors and in patient-derived models is not known. We integrate histology, transcriptome, exome, and treatment outcomes of SCLC from a range of metastatic sites, revealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 90 publications
3
54
0
Order By: Relevance
“…Furthermore, how specific mutations influence the subtype landscape remains unclear. NE tumors are enriched for alterations in RB1, NOTCH1, MYCL1 , and chromatin modifier genes and these NE tumors may have improved responses to replication stress inhibitors and poorer responses to ICI therapy compared to non-NE tumors (14). However, in this same study, there were no differences in overall survival between patients with NE vs. non-NE tumors, suggesting that the transcriptomic type alone may be insufficient for stratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, how specific mutations influence the subtype landscape remains unclear. NE tumors are enriched for alterations in RB1, NOTCH1, MYCL1 , and chromatin modifier genes and these NE tumors may have improved responses to replication stress inhibitors and poorer responses to ICI therapy compared to non-NE tumors (14). However, in this same study, there were no differences in overall survival between patients with NE vs. non-NE tumors, suggesting that the transcriptomic type alone may be insufficient for stratification.…”
Section: Discussionmentioning
confidence: 99%
“…The largest published study thus far included genome sequencing of 110 SCLC genomes from resected tumors (7). Combining this study and other smaller studies with more limited genomic analyses (e.g., whole-exome sequencing and targeted sequencing such as in (8-14)), it may be possible to get an estimate of genetic alterations in a few hundred patients at best. In addition, the disparate platforms used in these different studies makes it difficult to analyze the data as a group.…”
Section: Introductionmentioning
confidence: 99%
“…However, transcription factor profiling in clinical tumor samples is challenging, particularly for cancers with limited access to tumor specimens. Recent studies have revealed subtypes of SCLC, the most lethal type of lung cancer, defined by expression of lineage-defining transcription factors and their unique therapeutic vulnerabilities [14][15][16][17][18] . Yet, further testing and broad clinical application of these findings is limited by the availability of tumor tissue, explained by its widely metastatic presentation and aggressive clinical course which precludes surgical resection at diagnosis and tumor biopsies at relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reveal that SCLC tumors are transcriptionally heterogeneous 18,38,39 . We sought to understand whether cfChIP-seq reflects gene expression patterns of SCLC tumors.…”
Section: Plasma Cfchip-seq Informs Tumor Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation